Sampling plans for aphids and their parasitoids in blueberry fields in Argentina - Rocca, Margarita (2012)
Densities of aphids (Aphis gossypii and A. spiraecola) and mummified aphids at different phenological stages of a blueberry crop were estimated for the purpose of developing sampling plans. Our data set comprised 99 samples taken during the period 2006–2008 in four fields in Buenos Aires Province, Argentina. Estimation of population density based on the proportion of sample units infested by individuals was investigated. We also calculated the minimum number of sample units to estimate the density of individuals on buds and buds þ flowers using enumerative sampling. The relative precision of both methods was compared. Moreover, an enumerative sequential sampling protocol was developed. The presence–absence sampling plan gave density estimates with large variances (as measured by confidence intervals and large standard errors). The aggregation of mummies was similar on buds and buds þ flowers, so the required number of sample units for density estimates was the same. Relative precision of estimates was much lower for the presence–absence sampling than the enumerative sampling, even at intermediate densities. An enumerative sequential plan would be the most appropriate and useful method in management plans for aphids and mummified aphids in blueberries.